2019
DOI: 10.1016/j.jssr.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Critically Civic Teacher Perception, Posture and Pedagogy: Negating Civic Archetypes

Abstract: Critical pedagogy is an optimistic approach for achieving transformative agency, which remains an elusive and vital aspect of civic education. Therefore, the purpose of this study was to examine the pedagogical approach of three critically identifying teachers. Specifically, this study was interested in understanding participant teacher critically civic ontological postures. The posture implies an understanding of the power inherent to civic relation and pedagogy. Participant teachers uniquely demonstrated pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Dialogue is an important social studies skill that provides opportunities for students and teachers to increase critical thinking abilities, cultivate intercultural perspectives, and foster civic skills (Parker, 2003). Scholars have noted that dialogical practices can lead to more humanizing experiences in specifically socially just ways as students are provided spaces to rationalize social problems, reveal internalized identities, and grapple with problematic epistemological and ontological norms (Avery et al, 2013;Magill, 2018;Subedi, 2018). For these and other reasons, civic dialogue is commonly understood as a prerequisite skill for engaging in democratic citizenship (Barber, 1994;McCoy & Scully, 2002).…”
Section: Literature Review Social Studies and Dialoguementioning
confidence: 99%
See 1 more Smart Citation
“…Dialogue is an important social studies skill that provides opportunities for students and teachers to increase critical thinking abilities, cultivate intercultural perspectives, and foster civic skills (Parker, 2003). Scholars have noted that dialogical practices can lead to more humanizing experiences in specifically socially just ways as students are provided spaces to rationalize social problems, reveal internalized identities, and grapple with problematic epistemological and ontological norms (Avery et al, 2013;Magill, 2018;Subedi, 2018). For these and other reasons, civic dialogue is commonly understood as a prerequisite skill for engaging in democratic citizenship (Barber, 1994;McCoy & Scully, 2002).…”
Section: Literature Review Social Studies and Dialoguementioning
confidence: 99%
“…Social studies scholars have suggested that dialogue is vital to helping students develop the skills and disposition for becoming engaged civic participants (Magill, 2018;Parker & Hess, 2001;Subedi, 2008). However, research also notes that a theory practice gap exists between these beneficial interactions and their inclusion as part of a social studies teacher practice (Tannebaum, 2013).…”
mentioning
confidence: 99%
“…A critical focus, artifact analysis, and dialogue might provide a space for students to critically interpret culture (Magill, 2019; Cervantes-Soon et al, 2017; Freire, 1993). Simulations can provide such a context for teachers and their students to have these experiences.…”
Section: Ideology and Teacher Educationmentioning
confidence: 99%
“…As pre-service teachers become more aware of the dialectical tensions associated with social life, they can begin to engage in more meaningful inquiries and complex historical, sociological and economic interpretations. These inquiries and understandings can become foundations for critical dialogical praxis (Magill andRodriguez, 2015A AND 2015B;Magill and Rodriguez, forthcoming;McLaren, 1988). Without more critical framing of pedagogy and strong pedagogical content knowledge, teachers risk developing unsuccessful and problematic habits informing their practice.…”
Section: Critical Teacher Practices: Artifacts and Approachesmentioning
confidence: 99%
“…Fear of perceived political stances may lead administrators, parents or teachers to object to instruction around certain topics (Segall, 2003). Further, teachers may not be attuned to the political and lived experiences of their students, teaching an idealized curriculum though impersonal form of citizenship (Magill, 2018). Because of these and other teaching “norms,” teachers are often fearful of attending to differences and commonly succumb to self-defeating mechanisms associated with adopting hegemonic ideology (Gramsci, 1971; Magill and Salinas, 2019; McLaren, 1989; Segall, 2003).…”
Section: Fear Mentorship Ideology and Social Studies Teachingmentioning
confidence: 99%